Transitions between informal and formal jobs in India: Patterns, correlates, and consequences - Rajesh Raj Natarajan; Simone Schotte; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The Indian labour market is characterized by a high level of informality, with large numbers of workers in poorly paid 'lower-tier' informal jobs, and somewhat better paid 'uppertier' informal jobs, which do not have the same benefits and security of tenure as formal jobs. We examine the likelihood of individuals moving up from informal jobs to formal jobs (and vice versa) and from lower-tier to upper-tier informal jobs using a longitudinal dataset for India. We find that self-employed workers exhibit relatively more mobility than wage workers. Among wage workers, we find high persistence rates for formal wage employed and lower-tier informal wage employed. As expected, our results suggest substantial income gains for workers experiencing upward transition. Our results also suggest that lower-tier informal workers, whether in self-employment or wage employment, have limited upward transition possibilities, and are in a 'dead-end' work status.
Keywords: J21; J62; O17; 330; informal; formal; lower tier; upper tier; work status; India